answer; (x, y) = 16/11
I may be wrong but here how I got this answer.
y = 3x + 5 y = 2x + 4
{ y = 2 x + 4
{3x + 5 y = 2x + 4
{ y = 2 x + 4
{ 3x + 5 y = 2x + 4
then simplify now.
{-2 x + y = 4
{3 x + 5 y = 2x + 4 |
|
|
{ - 2 x + y = 4
{ x + 5y = 4
Multiply 2 by both sides
{-2 x + y = y
{ 2x + 10 y = 8
Sum the equation to eliminate at least one variable
11 y = 12
Divide both sides of the equation by 11
y = 12/11
Substitute the given value of y into the equation -2 x + y = 4
-2 + 12/11 = 4
X = - 16/11 you solve the x and you will get that answer